1999
DOI: 10.1046/j.1523-1739.1999.98338.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Surrogate Species in Conservation Biology

Abstract: Conservation biologists have used surrogate species as a shortcut to monitor or solve conservation problems. Indicator species have been used to assess the magnitude of anthropogenic disturbance, to monitor population trends in other species, and to locate areas of high regional biodiversity. Umbrella species have been used to delineate the type of habitat or size of area for protection, and flagship species have been employed to attract public attention. Unfortunately, there has been considerable confusion ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
556
0
18

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 781 publications
(576 citation statements)
references
References 69 publications
2
556
0
18
Order By: Relevance
“…As this study shows, that would mean that an area exceptionally rich in tree species would lose its protected status. We therefore argue caution in using limited biodiversity data as a basis for protected area management decisions and join with other authors (Prendergast and Eversham 1997;Caro and O'Doherty 1999;Lindenmayer et al 2002;Hess et al 2006) to caution against the use of indicator taxa as surrogates for biodiversity at fine levels of spatial scale.…”
Section: Conservation Implicationsmentioning
confidence: 92%
“…As this study shows, that would mean that an area exceptionally rich in tree species would lose its protected status. We therefore argue caution in using limited biodiversity data as a basis for protected area management decisions and join with other authors (Prendergast and Eversham 1997;Caro and O'Doherty 1999;Lindenmayer et al 2002;Hess et al 2006) to caution against the use of indicator taxa as surrogates for biodiversity at fine levels of spatial scale.…”
Section: Conservation Implicationsmentioning
confidence: 92%
“…Key species or guilds that are representative of different functional groups are known in most systems and appropriate surrogates can therefore be selected. Despite recognized limitations 31 , the application of the surrogate concept is widely applied in related fields including regulatory toxicity testing 28,29,32,33 and environmental monitoring [34][35][36] . In addition, the risk assessment may consider species with special aesthetic or cultural value or species classified as threatened or endangered.…”
Section: Species Selectionmentioning
confidence: 99%
“…In addressing whether the use of a charismatic species can influence attitudes towards habitats, it was necessary to select a suitable flagship species according to the selection criteria provided by the qualitative phase. Although it has been suggested that it may be difficult to identify a species featuring all of the desirable characteristics of a flagship species (Simberloff 1998;Caro & O'Doherty 1999;Caro et al 2004), we chose the great spotted woodpecker as a suitable candidate. Woodpeckers are found throughout the study area, are not commonly seen yet remain visible, are medium-sized birds, and are perceived to be compatible with humans.…”
Section: Citymentioning
confidence: 99%